Green Computing: Transforming Technology through Sustainable Innovation - Kapil Manshani, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and impact of green computing in transforming technology through sustainable innovation. The article examines the multifaceted approach to environmental sustainability in computing, encompassing hardware innovations, software optimization, and emerging technologies. It shows advanced processor architectures, energy-efficient storage solutions, and innovative cooling technologies while analyzing the transformation of software development through energy-aware programming practices and power management algorithms. It delves into integrating artificial intelligence, quantum computing, and IoT technologies in advancing sustainable computing practices. It also evaluates industry standards, economic implications, and corporate sustainability initiatives in the green computing sector. Through detailed analysis of implementation strategies, market opportunities, and regulatory frameworks, the article highlights the critical role of sustainable computing in addressing environmental challenges. The findings emphasize the importance of collaborative efforts across industry sectors and the need for balanced approaches in achieving technological advancement and environmental responsibility.
Keywords: Environmental Computing; Energy Efficiency; Green Computing; Power Management Systems; Sustainable Technology